A multianalyte fluorescent carbon dots sensing system constructed based on specific recognition of Fe(iii) ions. Issue 46 (31st May 2017) - Song, Pei; Zhang, Lisha; Long, Hao; Meng, Meng; Liu, Ting; Yin, Yongmei; Xi, Rimo
Abstract : A multianalyte fluorescent CDs sensing system for sensing Fe(iii ), H2 O2, and glucose. Abstract : In this research, we developed a multianalyte fluorescence sensing system through a carbon dots (CDs)-based fluorescent probe that can specifically recognize Fe(iii ) by fluorescence quenching. The CDs prepared using black tea by a hydrothermal method show outstanding properties like low cytotoxicity, high photostability, excellent biocompatibility, and high sensitivity. It was found that the fluorescence of CDs can be quenched by micromolar concentrations of Fe(iii ) in both aqueous solutions as well as living cells. It is well known that glucose can be oxidized by glucose oxidase (GOx) to release H2 O2, which, in turn, can oxidize Fe(ii ) to Fe(iii ). Based on this consideration, a multianalyte sensing system was established. Therefore the quantitative analysis of Fe(iii ), H2 O2, and glucose with detection limits of 0.25 μM, 0.82 μM, and 1.71 μM, respectively, was achieved by the simple and cost-effective multianalyte CDs sensing system constructed. The sensing system showed high photostability and negligible cytotoxicity toward HeLa cells, which enables it to be applied in the visualization of Fe(iii ) or H2 O2 in living cells. The system was further applied in the detection of Fe(iii ) or glucose in human serum, and satisfactory results were obtained.